PROGRAM RESTORASI LAHAN GAMBUT - Putri, Risky Arya; Rusli, Zaili Rusl; Yuliani, Febri (Jurnal Ilmu Administrasi Negara, 2018)
Pentland Restoration Program. The purpose of tbis research is to know the program of peatland restoration in Meranti Islands Regency. The research method used qualitative descriptive approach with the research informant of people involved in the implementation process of peat restoration in Meranti Islands Regency amounted to II people. Data collection techniques are interviews, observation and documentation. Data analysis used interactive methods ranging from data collection, data reduction, and conclusions. The result of this research is that so fur the effort of peatland restoration program in Meranti Islands Regency has not been realized thoroughly. This is influenced by a lack of understanding of the conceptualisation of peatland restoration programs, institutional preparedness and support of local, formal and informal figures at provincial, district and village levels.